18F-FDG PET/CT and 68Ga-DOTA-FAPI-04 PET/CT Findings of Myeloid Sarcoma. (11th March 2023) - Liu, Wei; Yang, Xiao; Chen, Liming; Chen, Yue; Xu, Tingting
Abstract: A 28-year-old woman presented with a 2-month history of swelling and pain in the chest wall. An irregular soft tissue mass in the chest wall and mediastinum was showed on chest CT. 18 F-FDG PET/CT revealed obvious FDG uptake in the mass. Subsequently, the patient was participated in a 68 Ga-DOTA-FAPI-04 PET/CT tumor clinical trial. 68 Ga-DOTA-FAPI-04 PET/CT also showed elevated tracer uptake in the mass. Biopsy of the mass confirmed a diagnosis of myeloid sarcoma.